2011
DOI: 10.1248/bpb.34.92
|View full text |Cite
|
Sign up to set email alerts
|

Parkinsonian Rotenone Mouse Model: Reevaluation of Long-Term Administration of Rotenone in C57BL/6 Mice

Abstract: Chronic systemic exposure of Lewis rats to rotenone produced many features of Parkinson's disease (PD), including nigrostriatal dopamine (DA) neurodegeneration and the formation of cytoplasmic inclusions in nigral DA neurons. We also reported that chronic oral administration of rotenone at 30 mg/kg for 28 d caused specific nigrostriatal DA neurodegeneration in C57BL/6 mice. To establish a PD model more suitable for evaluating nigrostriatal DA neurodegeneration, the present study has been designed to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
104
3
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(123 citation statements)
references
References 29 publications
11
104
3
3
Order By: Relevance
“…Inden and colleagues showed that chronic oral administration of rotenone at 30 mg/kg for 56 days in C57BL/6 mice caused a significant and selective loss of nigral DA neurons and induced behavioral impairment. In addition, a-synuclein immunoreactive cytoplasmic inclusions similar to Lewy bodies were observed in surviving DA neurons in a time-dependent manner (47). This recently optimized mouse rotenone model may thus provide a powerful model system in which to study gene-environment interactions if the chronic rotenone regimen is used in mice that are transgenic for genes linked to human PD.…”
Section: Rotenone Models Of Parkinsonismmentioning
confidence: 98%
“…Inden and colleagues showed that chronic oral administration of rotenone at 30 mg/kg for 56 days in C57BL/6 mice caused a significant and selective loss of nigral DA neurons and induced behavioral impairment. In addition, a-synuclein immunoreactive cytoplasmic inclusions similar to Lewy bodies were observed in surviving DA neurons in a time-dependent manner (47). This recently optimized mouse rotenone model may thus provide a powerful model system in which to study gene-environment interactions if the chronic rotenone regimen is used in mice that are transgenic for genes linked to human PD.…”
Section: Rotenone Models Of Parkinsonismmentioning
confidence: 98%
“…However, a major advantage of the 6-OHDA model is that it gives a quantifiable motor deficit (rotation) (37). On the other hand, we reported that chronic oral administration of rotenone caused specific nigrostriatal DA neurodegeneration in C57BL/6 mice (38,39). In rotenone-treated mice, α-synuclein immunoreactivity was increased in some surviving tyrosine hydroxylase (TH)-positive neurons in the substantia nigra.…”
Section: Introductionmentioning
confidence: 99%
“…The number of α-synuclein and TH double-positive neurons increased in a time-dependent manner. The previous experimental condition in the rotenone model may resemble early PD symptoms rather than atypical parkinsonism, although long-term treatment with rotenone is necessary (38,39). Therefore, in the present study, we used 6-OHDA-microinjected rats and rotenone-treated mice as acute and chronic animal models of PD, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In animals, rotenone has been administered by different routes. Oral administration appears to cause little neurotoxicity [84,85]. Chronic systemic administration using osmotic pumps has been the most common delivery regimen, especially in the Lewis rat, which may be more sensitive to rotenone than other strains of rats [86].…”
Section: Rotenonementioning
confidence: 99%
“…Attempts to lesion other animal species such as mice or monkeys have not been successful at all [72,92]. However, recent studies by two groups have demonstrated that oral administration of rotenone to mice causes nigral degeneration, a decrease of striatal dopamine levels, and motor dysfunction [85,93,94]. They also demonstrated α-synuclein aggregation in different areas of the brain [95].…”
Section: Rotenonementioning
confidence: 99%